Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2001
DOI: 10.1145/365024.365034
|View full text |Cite
|
Sign up to set email alerts
|

Cookies and Web browser design

Abstract: We first provide criteria for assessing informed consent online. Then we examine how cookie technology and Web browser designs have responded to concerns about informed consent. Specifically, we document relevant design changes in Netscape Navigator and Internet Explorer over a 5-year period, starting in 1995. Our retrospective analyses leads us to conclude that while cookie technology has improved over time regarding informed consent, some startling problems remain. We specify six of these problems and offer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…), whether to turn persistent cookies into session cookies, and whether to make decisions based on cookie-specific privacy policies or privacy policies for the broader website. Analyses of previous versions of browser cookie interfaces have found them to be inadequate [Millett et al 2001], and from the difficulties we observed users having in interpreting the IE6 preference configuration screen, it is clear that further work is needed to develop effective cookie interfaces.…”
Section: Summary Of Findings and Future Workmentioning
confidence: 95%
“…), whether to turn persistent cookies into session cookies, and whether to make decisions based on cookie-specific privacy policies or privacy policies for the broader website. Analyses of previous versions of browser cookie interfaces have found them to be inadequate [Millett et al 2001], and from the difficulties we observed users having in interpreting the IE6 preference configuration screen, it is clear that further work is needed to develop effective cookie interfaces.…”
Section: Summary Of Findings and Future Workmentioning
confidence: 95%
“…Cookies were initially developed to allow users to re-visit websites without the need to identify themselves and their preferences each time. However, in subsequent years cookies have been used in other ways, including in personalization processes (Millett, Friedman, & Felten, 2001). Personalization is initiated by a commercial entity, aiming to offer the customer products and services that best suited him/her, based on previously collected data (Li & Unger, 2012).…”
Section: Related Work Personalization and Customization In A Privacy mentioning
confidence: 99%
“…Personalization is initiated by a commercial entity, aiming to offer the customer products and services that best suited him/her, based on previously collected data (Li & Unger, 2012). This may bear different benefits for both the consumer and the vendor, however cookies that enable personalization might also be used in ways that invade users' privacy, for example third party websites use cookies to create user profiles without their knowledge and track users' online activities (Millett et al, 2001;Milne, 2000).…”
Section: Related Work Personalization and Customization In A Privacy mentioning
confidence: 99%
“…Cookies were initially developed to allow users to revisit websites without the need to identify themselves and their preferences each time. However, in subsequent years cookies have been used in other ways, including in personalization processes (Millett et al, 2001).…”
Section: Privacy Issues and Personalizationmentioning
confidence: 99%
“…Personalization is used many times by commercial entities, offering customers products and services that best suit them, based on previously collected data (Li and Unger, 2012). This method may benefit both the consumer and the vendor; however, cookies that enable personalization might also be used in ways that invade users' privacy, for example, thirdparty websites use cookies to create user profiles without their knowledge and track users' online activities (Millett et al, 2001;Milne, 2000).…”
Section: Privacy Issues and Personalizationmentioning
confidence: 99%